Cocaine amphetamine-regulated transcription peptide inhibits apoptosis in oxygen–glucose deprived neural stem cells - Zhang, Lu; Chen, Shan; Zou, Renfang; Shu, Xin; Zhang, Jingxuan; He, Xuan; Su, Moxi; Wang, Luna; Wang, Bin; Sha, Dujuan (Frontiers in Neuroscience, 2024)
Background: Apoptosis has been recognized as a critical pathophysiological process during cerebral ischemia. The neuroprotective effect of CART on ischemic brain injury is determined. However, there is little research on the protective effect of CART on neural stem cells (NSCs).Methods: Primary cultured rat NSCs were utilized as the research subject. In vitro oxygen glucose deprivation (OGD) treatment was employed, and NSCs were extracted from SD pregnant rats following previous experimental protocols and identified through cell immunofluorescence staining.The appropriate concentration of CART affecting OGD NSCs was initially screened using Cell Counting Kit-8 (CCK-8) and Lactate Dehydrogenase (LDH) assays. EdU staining and Western blotting (WB) techniques were employed to assess the impact of the suitable CART concentration on the proliferation and apoptosis of OGD NSCs. Finally, Western blot analysis was conducted to investigate the cAMP-response element binding protein (CREB) pathway and expression levels of related proteins after KG-501 treatment in order to elucidate the mechanism underlying apoptosis and proliferation regulation in OGD NSCs.Results: CCK-8 and LDH assays indicated that a concentration of 0.8nM CART may be the optimal concentration for modulating the proliferation of OGD NSCs. Subsequently, cellular immunofluorescence and EdU detection experiments further confirmed the findings obtained from CCK-8 analysis. Western blot analysis of apoptosis-related protein expression also demonstrated that an appropriate concentration of CART could suppress the apoptosis of OGD NSCs. Finally, Western blotting was conducted to examine the CREB pathway and related protein expression after treatment with KG-501, revealing that an appropriate concentration of CART regulated both apoptosis and proliferation in OGD NSCs through CREB signaling.The concentration of CART at 0.8nM may be deemed appropriate for inhibiting apoptosis and promoting proliferation in OGD NSCs in vitro. The mechanism maybe through activating the CREB pathway.